Clinical Characteristics and Prognostic Analysis of Patients With Pulmonary Tuberculosis and Type 2 Diabetes Comorbidity in China: A Retrospective Analysis - Zhang, Shijie; Tong, Xiang; Wang, Lei; Zhang, Tianli; Huang, Jizhen; Wang, Dongguang; Wang, Lian; Fan, Hong (Frontiers in Public Health, 2021)
Background: Tuberculosis is one of the leading communicable disease, with significant morbidity and mortality. Diabetes can increase the risk of developing tuberculosis and the related adverse outcomes. This study retrospectively analyzed the clinical characteristics and prognosis of patients with pulmonary tuberculosis and type 2 diabetes comorbidity. Methods: 282 cases with pulmonary tuberculosis and type 2 diabetes comorbidity were identified from West China Hospital between January 1, 2010 and December 31, 2016 and were followed up for at least 3 years. We further used Kaplan-Meier methods and COX regression analysis to identify influence factors for all-cause death. Results: Compared to the survival patients, patients who died were older, exhibited significantly lower albumin and hemoglobin level, but higher Charlson Comorbidity Index (CCI) score at admission, and had lower usage rate of metformin. The all-cause mortality at 1-year and 5-year were 5.67% and 20.59%, separately. For 1-year all-cause death, higher albumin level (HR=0.90, 95% CI: 0.81-0.99) was the independently protective factor, but older age (HR=1.07, 95% CI: 1.01-1.13) and CCI score ≥3 (HR=6.77, 95% CI: 1.40-32.69) were the independently risk factors. For long-term all-cause death, higher albumin level (HR=0.94, 95% CI: 0.88-1.00), the use of metformin (HR=0.21, 95% CI: 0.07-0.59), insulin (HR=0.27, 95% CI: 0.10-0.74) or sulfonylureas (HR=0.23, 95% CI: 0.07-0.74) were the independently protective factors, but older age (HR=1.03, 95% CI: 1.00-1.07) and CCI score ≥3 (HR=7.15, 95% CI:2.56-19.92) were the independently risk factors. Conclusions: The lower albumin level, older age and CCI score ≥3 were predictors of all-cause death in patients with pulmonary tuberculosis and type 2 diabetes comorbidity. In the long run, patients who use metformin, insulin or sulfonylureas as hypoglycemic agents may have a lower incidence of death.